Spatial modeling of pyroclastic cover deposit thickness (depth to bedrock) in peri‐volcanic areas of Campania (southern Italy). Issue 9 (7th March 2018) - Del Soldato, Matteo; Pazzi, Veronica; Segoni, Samuele; De Vita, Pantaleone; Tofani, Veronica; Moretti, Sandro
Abstract: In this study, the main focus is the application and improvement of four empirical models, which account for the pyroclastic cover deposit thickness (PCDT) spatial distribution with respect to the bedrock surrounding the Somma‐Vesuvius volcano (Campania, southern Italy). Three models, which are already known in the literature, link the depth to bedrock to the morphological features of a slope. An original model called SEPT (slope exponential pyroclastic thickness) is presented in this manuscript and combines the initial total thickness of ash‐fall pyroclastic cover with the slope gradient. All models were applied and validated using field measurements derived from this and preceding studies in the study area. The main finding is that the spatial distribution of the depth to bedrock in mountainous peri‐volcanic areas mainly depends on the initial thickness of air‐fallen material at a given position and slope angle. These findings allowed for the recognition of an ash‐fall pyroclastic depositional environment that is characterized by different processes from those existing in other geomorphological frameworks and in which the soil thickness along the slopes is controlled by the weathering of bedrock and the formation of soil in situ . Finally, in this research, a reliable approach is proposed that is also applicable to other peri‐volcanic areas of the world to assess the spatial distribution of the depth to bedrock, which is a fundamentally important parameter in distributed geomorphologic and hydrologic modeling. © 2018 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : The study focuses on the application and improvement of three state‐of‐the‐art empirical models in order to propose a new approach accounting for the spatial distribution of PCDT (pyroclastic cover deposit thickness), an important parameter for the distributed geomorphologic and hydrologic modeling. The test site is the surrounding area of the Somma‐Vesuvius volcano (Campania, southern Italy). The results were critically compared and statistical analyzed with respect to about 300 direct and indirect measurements.